E professo viver e morrer em santa fé católica: atitudes diante da morte em uma freguesia de Vila Rica na primeira metade do século XVIII - Denise Aparecida Sousa Duarte (2013)
This dissertation aims to analyze an aspect of major relevance for religious life in Vila Rica during the first half of the 18th century: death-related practices. Focusing on this practices, specifically on people who wrote their testaments at that time, we intend to interpret the endless search of those men for their souls salvation, based on certain procedures discriminated by the Catholic Church as capable of assisting the achievement of sins forgiveness and making easier the achievement of eternal glory in Paradise. We consider that this pacifying rethoric was the main motivation for performance of these practices, once it gave emphasis on hope and encouraged the churchgoers to have faith on their salvation. Thus, we examine the proximity between written wills (and also the death registers of some of these men who made testaments) and the assertion of religious principles, falling back upon printed religious documents and other manuscript sources which ruled the behavior of churchgoers towards death. In explaining how such prescriptions were important for these churchgoers, we intend to achieve a wider reflection about religiosity in Minas, which is described by great part of historiography related to this subject as dissonant from doctrine based principles.